Smart Village Initiative for Drug-Free Communities: A Technology-Based Approach in West Java - Ismail, Ismail; Felecia, Felecia; Azizah, Anisa Kurniatul; Rahmawati, Diana (West Science Information System and Technology, 2025)
The Smart Village Initiative in West Java leverages technology to combat drug-related issues and foster drug-free communities. This study employs a quantitative analysis with 150 respondents using a Likert scale (1–5), analyzed via Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that technological interventions significantly enhance drug prevention outcomes and community engagement, with community engagement mediating the relationship between technology and outcomes. The results demonstrate the initiative's effectiveness in promoting awareness, participation, and safety within communities. These findings underscore the potential of integrating technology and community-driven approaches to address complex social issues, offering a scalable model for other regions. Future research should explore long-term impacts and adaptations for diverse contexts.